√ 25 –2√3 + √27 +2√ 9 Express in simplified radical
![25 23 27 2 9 Express in simplified radical class=](https://us-static.z-dn.net/files/df2/b9ff2001a1ee226c4c935f2dc2a2aaf7.png)
Answer:
The expression in simplified radical form is:
√ 25 –2√3 + √27 +2√ 9 = 11 + √3
Step-by-step explanation:
Given the expression
√ 25 –2√3 + √27 +2√ 9
as
√ 25 = 5
√27 = 3√3
2√9 = 6
so the expression becomes
√ 25 –2√3 + √27 +2√ 9
= 5 - 2√3 + 3√3 + 6
= 11 + √3
Thus, the expression in simplified radical form is:
√ 25 –2√3 + √27 +2√ 9 = 11 + √3